Effectiveness of Marital Psycho-Spiritual Intervention (MP-SI) on communication among Muslim husbands and wives - Ahmad, Rosliza; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The aim of this study is to investigate the effectiveness of Marital Psycho-Spiritual Intervention (MP-SI) on communication among Muslim husbands and wives at Felda in Kedah. The randomized controlled trials (randomized control group design with pretest, posttest and follow up test) was used in this study. The experimental and control group of this study composed of a total of 76 participants, 38 in experimental group and 38 in control group. Participants in experimental group received a treatment of MP-SI for 6 weeks (2 hours per week). Marital Communication Inventory (MCI) was utilized to obtain the data for communication in three times (pretest, posttest, and follow up). A Mixed Between-Within Subjects ANOVA was used to test the differences between the mean scores of pretest, posttest, and follow up test within both experimental and control group. The findings of this study indicate that there are significant main effect of time F (2, 73) = 32.31, p < .05, main effect of group F (1, 74) = 15.37, p < .05, and interaction effects for time and group, F (2, 73) = 22.75, p < .05. The findings revealed that communication among Muslim husbands and wives was significantly improved with the treatment of MP-SI.